The Effect of Occupational Art Therapy on Depression, Anxiety and Stress in the Elderly in Nursing Homes: A Quasi-Experimental Study - Laela Megasari, Anis; Subekti Wulandari, Ika; Najwatul Maula , Sheyla (Chakra Brahmanda Lentera Institute, 2024)
Background: Elderly individuals residing in care facilities possess the potential for low physical activity, frequent illness, a hostile environment, and a lack of self-confidence, causing older people to become anxious, stressed, and even depressed. Unfortunately, no intervention can overcome this problem. Occupational art therapy involves using artistic mediums as a form of treatment and creative processes to help express oneself, improve individual physical and coping skills, manage stress, and strengthen self-confidence. Methods: This research aims to explain the effect of occupational art therapy on depression, stress, and anxiety in older adults in nursing homes. This research uses a quasi-experimental pre and post-test design. The total sample used was 60 respondents, who were divided into intervention and control groups using a sampling technique, namely purposive sampling. Data were collected using the short version of the Depression Anxiety and Stress Scale (21 items). Descriptive statistics, frequency distribution, and Paired and Unpaired T-tests were applied for data analysis. Results: The findings of the research indicated that occupational arts therapy could reduce depression scores with an average difference of 8.63, namely an anxiety score of 5.54 and a stress score of 3.59. Data analysis showed that occupational art therapy significantly reduced anxiety, depression, and stress scores (p-value 0.000). Conclusion: Occupational art therapy can be used as a complementary therapy in nursing homes to reduce depression, anxiety, and stress in older people. The findings of this study are expected to help improve services in nursing homes, especially for reducing depression, anxiety, and stress in older people.